Implementasi Hybrid Cloud Berbasis NAS untuk Backup Otomatis Data Transaksi POS Qasir - Muhammad Rafif Ulwan; Desi Ramayanti (Riau Jurnal Teknik Informatika, 2026)
Vape Paradise relies on the Qasir Point of Sale (POS) application to manage sales transactions; however, transaction data is still backed up manually, increasing the risk of data loss and reducing data availability. Previous studies have mainly focused on Network Attached Storage (NAS) as a local storage solution, while the integration of NAS with automated cloud backup for retail transaction systems remains limited. Therefore, this study aims to implement a hybrid cloud backup system by integrating a Samba-based NAS with Google Drive to provide automated and reliable transaction data backup. The proposed system was developed through network design, NAS configuration, automated synchronization using Task Scheduler and Robocopy, and system testing. Experimental results demonstrate that transaction files were successfully synchronized automatically to both NAS and Google Drive, while network connectivity achieved 0% packet loss, indicating stable communication during the backup process. The proposed hybrid cloud backup system enhances data security, availability, and backup efficiency, providing a cost-effective solution for protecting transaction data in retail business environments.